Main Properties of Rainfed Typical Serozem Soils Distributed in Parkent District, Tashkent Region - Gulimov Quvondiq Xamzaevich; Bahodirov Zafar Abduvalievich; Ахмедов Алмон Усмонович (American Journal of Biology and Natural Sciences, 2025)
This article presents information on the current state, characteristics, mechanical composition, CO2 carbonates, and the amount of nutrients and humus in the rainfed typical serozem soils distributed in the Parkent district of the Tashkent region.